Ramanujan’s Tau-Function in Terms of Bell Polynomials (Indian Journal of Advanced Mathematics (IJAM), 2024)
We obtain a recurrence relation for the Ramanujan’s tau-function involving the sum of divisors function, and the solution of this recurrence gives a closed formula for r(n) in terms of the complete Bell polynomials.